Financial Book Keeping, And Online Marketing Training For Micro, Small And Medium Enterprises - Santi Riana Dewi; Andari Andari; Martina Rahmawati Masitoh; Santi Octaviani (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
Abstract At this time, micro, small and medium enterprises (MSMEs) are expected to be able to keep up with the times. Entering the industrial era 4.0, mastery of technology has an impact on shifts in service delivery and in the development of MSMEs in society. So that it is necessary to add and increase the potential of human resources in mastery of digital technology in the implementation of daily life and business. The problem in the location where we serve is that there are no business actors who master financial management and marketing management. So that our activities are focused on providing training in financial accounting and online marketing. By having good financial books, it can be used as consideration for submitting funding to financial institutions. In addition, to meet market expansion, digital marketing training is provided by marketing through social media, such as WhatsApp, Instagram, and Facebook. This is an active role of higher education through community service to participate in helping the government in reducing poverty, preventing technological failures, and improving community welfare independently in order to realize ideals or things that are the desire of the community in general. The implementation of the service begins with making a draft proposal, requesting permission, observation, socialization, counseling, workshops, training, presentation of results, product packaging, learning simple financial management, learning about marketing management, and evaluation. As for the results of the implementation of this service, the community is able to make financial report and market products through online media. Keywords: training, finance, marketing, online.